2017
DOI: 10.1037/emo0000244
|View full text |Cite
|
Sign up to set email alerts
|

How the social ecology and social situation shape individuals’ affect valence and arousal.

Abstract: Many theories highlight the role social contexts play in shaping affective experience. However, little is known about how individuals' social environments influence core affect on short time-scales (e.g., hours). Using experience sampling data from the iSAHIB, wherein 150 adults aged 18 to 89 years reported on 64,213 social interactions (average 6.92 per day, SD = 2.85) across 9 weeks of daily life, we examined how 4 features of individuals' social ecology (between-person differences) and immediate social situ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
35
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 81 publications
(125 reference statements)
6
35
1
Order By: Relevance
“…Since the semi-realistic and realistic agents are appeared to be same age group with the students, they could interact easily by accepting the virtual agents as their friend. The finding was consistent with findings of past studies by Vogel et al (2017) which supported that an individual seek for frequent interaction with close and highly familiar people.…”
Section: Hypothesissupporting
confidence: 93%
See 2 more Smart Citations
“…Since the semi-realistic and realistic agents are appeared to be same age group with the students, they could interact easily by accepting the virtual agents as their friend. The finding was consistent with findings of past studies by Vogel et al (2017) which supported that an individual seek for frequent interaction with close and highly familiar people.…”
Section: Hypothesissupporting
confidence: 93%
“…Indeed, higher feeling of excitement on the presently focused process can lead to achieve higher arousal without considering its later consequences [29]. Commonly, an individual seeks for frequent interaction with close and highly familiar people [30]. The communication with familiar people motivates an individual's behavior [31] and increases their arousal as well [30].…”
Section: B Arousalmentioning
confidence: 99%
See 1 more Smart Citation
“…There are many ways to define a (social) situation (Rauthmann et al, ), including the type of interaction partner (Chui, Hoppmann, Gerstorf, Walker, & Luszcz, ; Vogel, Ram, Conroy, Pincus, & Gerstorf, ), the place or activity (Wrzus et al, ), the purpose (McCabe & Fleeson, ), and the perceptions (Horstmann & Ziegler, ; Rauthmann et al, ; Sherman et al, ) and behaviours of the individuals involved (Côté & Moskowitz, ; Fournier, Moskowitz, & Zuroff, ; Pincus, ; Pincus, Hopwood, & Wright, ; Wang et al, ). However, in research designs where only the target person's perception is used to measure a situation, distinctions between person and situation variables can become blurred, because person variables may influence situation perception (cf.…”
Section: Personality–situation Fit and Momentary Happiness In Social mentioning
confidence: 99%
“…The existence of strong affect was most visible in situations when participants were around people closely connected to them. The highest PA in Study 1 was reported after participants talked to friends or family members, which supported existing research showing that, across cultures and in various age groups, being around and talking to family and friends leads to higher PA than being around co-workers, acquaintances, or strangers (Chui, Hoppmann, Gerstorf, Walker, & Luszcz, 2014;Coan et al, 2006;Cohen, 2004;Downie, Mageau, & Koestner, 2008;King & Reis, 2012;Mehl et al, 2010;Oishi, Napa Scollon, Diener, & Biswas-Diener, 2004;Vogel, Ram, Conroy, Pincus, & Gerstorf, 2017). However, being with people strongly connected to them but not talking to them, also resulted in participants reporting the highest momentary negative affect, although this difference was not statistically significant.…”
Section: Discussionsupporting
confidence: 84%